Channel kultura TV CCP's video series on Philippine broadcasting as a cultural force - Del Mundo, Clodualdo, Jr.; Del Mundo, Clodualdo, Jr.; Roa, Boots Anson; Salvador, Eva Mari G.; Cultural Center of the Philippines; National Commission for Culture and the Arts. (Manila Cultural Center of the Philippines, 2003)
A video documentary on the history of Philippine television.
Executive producer: Eva Mari G. Salvador ; narrator: Boots Anson-Roa.
VCD.
Accompanying CD of Telebisyon : an essay on Philippine television / Clodulado Del Mundo, Jr.
Keywords: Television broadcasting -- Philippines -- History; Television -- Philippines -- History